Employee Performance of Local Governments in Handling and Prevention of Child Violence - Yayuk Astuti; Sundari Sundari; Hardianti Hardianti (JIA: Jurnal Ilmiah Administrasi, 2023)
To explain relationship between accountability local governments and strategies for handling and preventing child violence. This article desbrice how to analyze the competence, accountability, strategies for handling and preventing child violence local governments. This research is based on the cluster analysis feature and the word frequency analysis feature on the NVivo-12 software based on reliable online news data. The results showed that the handling and prevention of children by local governments was not optimal. This is due to the weak competence of employees in the aspects of knowledge, skills and abilities. The accountability for the performance of local governments has not been effective, especially in the accountability of the process of handling cases of child violence. Strategies for handling and preventing cases of child violence have not maximally involved all stakeholders, therefore a partnership-based strategy is recommended as a solution to maximize the performance of local governments